A High-Density Genetic Linkage Map and QTL Mapping for Sex in Black Tiger Shrimp (Penaeus monodon) - Guo, Liang; Xu, Yu-Hui; Zhang, Nan; Zhou, Fa-Lin; Huang, Jian-Hua; Liu, Bao-Suo; Jiang, Shi-Gui; Zhang, Dian-Chang (Frontiers in Genetics, 2019)
The black tiger shrimp, Penaeus monodon, is important in both fishery and aquaculture and is the second-most widely cultured shrimp species in the world. However, the current strains cannot meet the market needs in various cultural environments, and the genome resources for Penaeus monodon are still lacking. Restriction-site associated DNA sequencing has been widely used in genetic linkage map construction and in quantitative trait loci mapping. We constructed a high-density genetic linkage map with restriction-site associated DNA sequencing in a full-sib family. This map contained 6524 single nucleotide polymorphisms and 2208 unique loci. The total length was 3275.4 cM, and the genetic distance was estimated to be 1.1 Mb per cM. The sex trait is a dichotomous phenotype, and the same interval was detected as a quantitative trait locus using quantitative trait loci mapping and genome-wide association analysis. The most significant locus explained 77.4% of the phenotype variance. The sex locus was speculated to be the same in this species based on the sequence alignments in Mozambique, India and Hawaii populations. The constructed genetic linkage map provided a valuable resource for quantitative trait loci mapping, genome assembly and genome comparison for shrimp. The demonstrated common sex locus is a step closer to locating the underlying gene.